Experimental investigation of water entry of bodies with constant deadrise angles under hydrophobic effects - Guzel, Bulent; Korkmaz, Fatih C. (SPRINGER, 2021)
The effects of hydrophobicity on free surface elevation and impact loads are experimentally investigated during the water entry of wedges and cones with various deadrise angles, with particular attention given to the early stages of the impact. As opposed to spheres and cylinders, there is no Froude number dependency and hydrophobicity is not associated only with cavity formation, since a cavity is created at any velocity and at any contact angle in case of wedges and cones. It is observed that the formation of the jet flow, pileups and cavities during the water entry of the objects with constant deadrise angles are modified under the hydrophobic effects. There is no flow separation and the jet root travels faster along the solid surface and larger pileups with larger wetting factors change the chine wetting time resulting in smaller magnitudes when hydrophobicity is present. The slamming coefficient values under hydrophobic effects are measured about 10-25% smaller than the ones obtained with hydrophilic surfaces. Hydrophobic effects are stronger at smaller deadrise angles. It is also shown that the wetted length depends not only on the geometry but also the solid surface characteristics, and the amount of added mass is not proportional to the wetted area and may be decreased with increased wetted width depending on the contact angle. [GRAPHICS] .
Keywords: IMPACT; SPHERES; SURFACE; FLUID; LOADS; MODEL; Engineering; Mechanics